E-175 Telemedicine during and post-covid 19: the insights of neurosurgery patients and physicians. (23rd July 2022) - El Naamani, K; Abbas, R; Mukhtar, S; El Fadel, O; Sathe, A; Kazan, A; El Hajjar, R; Sioutas, G; Tjoumakaris, S; Bhaskar, S; Herial, N; Gooch, M; et al.
Abstract : Background: COVID-19 has caused massive surge in telemedicine utilization as patients and physicians tried to minimize in-person contact to avoid the spread and impact of the pandemic. Objective: This study aims to expand on the knowledge of telemedicine during and beyond the COVID-19 era as it pertains to its use, efficacy, and patient and provider satisfaction through surveys sent to patients and neurosurgery physicians. Methods: This is a retrospective study involving 93 patients and 33 Neurosurgery physicians who anonymously participated in the surveys about their experience with telemedicine visits. Results: Most respondents indicated extreme satisfaction with their telemedicine encounters during the pandemic (77%). As for how comfortable physicians are in providing a diagnosis via telemedicine compared to clinic visits, 7 (21.9%) physicians felt extremely comfortable, 13 (40.6%) felt somewhat comfortable, 2 (6.4%) were neutral, 9 (28.1%) felt somewhat uncomfortable and 1 (3.1%) felt extremely uncomfortable. Physical examination was the main tool that telemedicine didn't provide (n=21, 100%). When presented with the statement that telemedicine should remain as an option for medical appointments in the post-Covid era, most respondents strongly agreed (n=71, 81.6%). As for the option of telemedicine replacing clinic visits, 16 (18.4%) respondents said they strongly agree with the proposition, 17 (19.5%) said they agree, 13 (14.9%) said they were neutral, 22 (25.4%) said they disagree, and 19 (21.8%) said they strongly disagree . Conclusion: Telemedicine has become a major force in the health care system under the circumstances the world is witnessing. Physicians and patients have displayed high levels of satisfaction with telemedicine which could be pivotal to improving healthcare access to underprivileged areas beyond the pandemic. Disclosures: K. El Naamani: None. R. Abbas: None. S. Mukhtar: None. O. El Fadel: None. A. Sathe: None. A. Kazan: None. R. El Hajjar: None. G. Sioutas: None. S. Tjoumakaris: 2; C; Medtronic, Microvention. S. Bhaskar: None. N. Herial: None. M. Gooch: 2; C; Stryker. R. Rosenwasser: None. P. Jabbour: 2; C; Medtronic, Microvention, Balt, Cerus Ednovascular.